Genomic characterisation of the population structure and antibiotic resistance of Salmonella enterica serovar Infantis in Chile, 2009-2022Research in context - Alejandro Piña-Iturbe; Constanza Díaz-Gavidia; Francisca P. Álvarez; Rocio Barron-Montenegro; Diana M. Álvarez-Espejo; Patricia García; Doina Solís; Rodrigo Constenla-Albornoz; Magaly Toro; Jorge Olivares-Pacheco; Angélica Reyes-Jara; Jianghong Meng; et al. (Elsevier, 2024)
Summary: Background: Multidrug-resistant (MDR) Salmonella Infantis has disseminated worldwide, mainly linked to the consumption of poultry products. Evidence shows dissemination of this pathogen in Chile; however, studies are primarily limited to phenotypic data or involve few isolates. As human cases of Salmonella Infantis infections have substantially increased in recent years, this study aimed to characterise the genomic epidemiology and antimicrobial-resistance profiles of isolates obtained from different sources, aiming to inform effective surveillance and control measures. Methods: We sequenced 396 Salmonella Infantis genomes and analysed them with all publicly available genomes of this pathogen from Chile (440 genomes in total), representing isolates from environmental, food, animal, and human sources obtained from 2009 to 2022. Based on bioinformatic and phenotypic methods, we assessed the population structure, dissemination among different niches, and antimicrobial resistance (AMR) profiles of Salmonella Infantis in the country. Findings: The genomic and phylogenetic analyses showed that Salmonella Infantis from Chile comprised several clusters of highly related isolates dominated by sequence type 32. The HC20_343 cluster grouped an important proportion of all isolates. This was the only cluster associated with pESI-like megaplasmids, and up to 12 acquired AMR genes/mutations predicted to result in an MDR phenotype. Accordingly, antimicrobial-susceptibility testing revealed a strong concordance between the AMR genetic determinants and their matching phenotypic expression, indicating that a significant proportion of HC20_343 isolates produce extended-spectrum β-lactamases and have intermediate fluoroquinolone resistance. HC20_343 Salmonella Infantis were spread among environmental, animal, food, and human niches, showing a close relationship between isolates from different years and sources, and a low intra-source genomic diversity. Interpretation: Our findings show a widespread dissemination of MDR Salmonella Infantis from the HC20_343 cluster in Chile. The high proportion of isolates with resistance to first-line antibiotics and the evidence of active transmission between the environment, animals, food, and humans highlight the urgency of improved surveillance and control measures in the country. As HC20_343 isolates predominate in the Americas, our results suggest a high prevalence of ESBL-producing Salmonella Infantis with intermediate fluoroquinolone resistance in the continent. Funding: Partially supported by the Food and Drug Administration (FDA) of the U.S. Department of Health and Human Services as part of an award, FDU001818, with 30% percent funded by FDA/HHS; and by Agencia de Investigación y Desarrollo de Chile (ANID) through FONDECYT de Postdoctorado Folio 3230796 and Folio 3210317, FONDECYT Regular Folio 1231082, and ANID-Millennium Science Initiative Program-ICN2021_044.